Climate change, vulnerability and migration: - Climate change, vulnerability and migration
Contributed articles on the climate changes and migration challenegs in india presented at 'National Workshop on Migration and Global Environmental Change in India" 4-5 March 2014 at New Delhi organised by UNESCO New Delhi and Foresight, United Kingdom ; some papers are also from International Seminar on 'Migration, Care Economy, and Development' organized at Centre for Development Studies, Thiruvananthapuram, Kerala.